Identification of LncRNA Prognostic Markers for Ovarian Cancer by Integration of Co-expression and CeRNA Network - Liang, Huisheng; Bai, Yuquan; Wang, Hailong; Yang, Xiangjun (Frontiers in Genetics, 2021)
Background: Ovarian cancer (OC) is one of the most prevalent gynecological malignant cancers, and is characterized by late detection and dismal prognosis. Recent researches show that long non-coding RNAs (lncRNAs) in competitive endogenous RNA (ceRNA) network plays a crucial role in the immune infiltration and prognosis of cancer. However, the biological function of lncRNA in the immune infiltration and prognosis of OC remains unclear. Methods: Ovarian cancer (OC) is one of the most prevalent gynecological malignant cancers, and is characterized by late detection and dismal prognosis. Recent researches show that long non-coding RNAs (lncRNAs) in competitive endogenous RNA (ceRNA) network plays a crucial role in the immune infiltration and prognosis of cancer. However, the biological function of lncRNA in the immune infiltration and prognosis of OC remains unclear. Results: We found that lncRNAs and mRNAs in the brown module were significantly associated with the immune cells in OC, and four lncRNAs were identified as potential prognostic markers of OC prognosis. We further established that lncRNAs in the ceRNA influence immune infiltration and prognosis of OC by regulating miRNA and ultimately targeting mRNA. Conclusions: We have identified four lncRNAs as independent immune prognostic factors for OC. Furthermore, our study provides a novel insight into the use of lncRNAs as immune and prognostic markers of OC.